The Caregiver Burden of Mothers of Patients Who Received Tracheostomy in a University Hospital Pediatric Intensive Care Unit - Dilek Öztoprak Hacıoğlu; Caner Hacıoğlu; Ökkeş Özgür Mart; Dinçer Yıldızdaş (Galenos Yayinevi, 2022)
Introduction:The aim of this study was to determine the caregiver burden of mothers of patients who were treated in a university hospital pediatric intensive care unit and had tracheostomy.Methods:The mothers of 41 patients who were hospitalized and received tracheostomy at Çukurova University Medical Faculty Pediatric Intensive Care Unit between 10.06.2020-31.12.2020 were included in the study. A data collection form consisting of three parts was used to collect the data. With the "caregiver and socio-demographic information form" in the first section, the data belonging to the mother and family were obtained. With the "care given information form" in the second section, the data belonging to the child with tracheostomy were obtained. With the "caregiver burden inventory" in the third section, the caregiver burden of mothers was determined.Results:The mean caregiver burden total score of the mothers was 40.2±14.3 (16.0-81.75). The caregiver burden sub-scores were detected from the highest to the lowest in the form of timedependence burden, developmental burden, physical burden, social burden and emotional burden. The caregiver burden total score was found significantly higher in mothers whose families receive economic support, who have health problems after their child's tracheostomy care has started, who have difficulties in caring for their children, who have difficulties in meeting the needs of other members of their family.Conclusion:It is of great importance to reduce the caregiver burden of mothers who care for children with tracheostomy to provide effective care and to protect and improve the health status of both the mother and the child with tracheostomy.